Quality and safety in nursing : a competency approach to improving outcomes - Sherwood, Gwen; Barnsteiner, Jane Herman (John Wiley & Sons, Inc., 2017)
Drawing on the universal values in health care, the second edition of Quality and Safety in Nursing continues to devote itself to the nursing community and explores their role in improving quality of care and patient safety.